2021
DOI: 10.1063/5.0050747
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of flow dynamics and mechanical retention of surface-altered red blood cells through a splenic slit

Abstract: Normal red blood cells (RBCs) have remarkable properties of deformability, which enable them to squeeze through tiny splenic inter-endothelial slits (IESs) without any damage. Decreased surface-area-to-volume (SA/V) ratio through the loss of membrane surface is a key determinant of splenic entrapment of surface-altered RBCs due to cell aging or disease. Here, we investigate the flow dynamics and mechanical retention of the surface-altered RBCs with different extents of surface area loss, using a multiscale RBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…As RBCs age, their deformability decreases primarily due to reduced S/V [82], increased membrane stiffness [83] and increased ratio of internal viscosity to external viscosity [84], see recent review in [85]. A number of experimental [29,86] and computational studies [14,48,50,51,87] have demonstrated that S/V plays a much more important role in dictating the passage or retention of RBCs through narrow slit than the other two factors. In particular, a recent ex vivo experimental study [86] reported that a solo increase in membrane stiffness of diamide-treated RBCs without decreasing their S/V was not associated with mechanical retention in the human spleen.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…As RBCs age, their deformability decreases primarily due to reduced S/V [82], increased membrane stiffness [83] and increased ratio of internal viscosity to external viscosity [84], see recent review in [85]. A number of experimental [29,86] and computational studies [14,48,50,51,87] have demonstrated that S/V plays a much more important role in dictating the passage or retention of RBCs through narrow slit than the other two factors. In particular, a recent ex vivo experimental study [86] reported that a solo increase in membrane stiffness of diamide-treated RBCs without decreasing their S/V was not associated with mechanical retention in the human spleen.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In addition, prior studies on the traversal of RBCs through IES mainly look into the RBC deformation dynamics and the conditions for RBC retention or passage without considering the alterations of retained RBCs at IES.In this work, we perform a systematic computational study to simulate the passage of RBCs at different stages of their lifespan through IES in the spleen, the most stringent challenge on RBCs' integrity and deformability in the human circulation. Different from prior computational work [14,[48][49][50][51], we primarily focus on simulating the alterations of reticulocytes and senescent RBCs when traversing IES, such as pitting, vesiculation and lysis, and explore the mechanism of the spleen in facilitating the maturation of reticulocytes as well as to examine the emerging hypothesis of intrasplenic hemolysis triggered by mechanical trapping of aged RBCs [34].…”
Section: Introductionmentioning
confidence: 99%
“…While in the particle-based methods, such as dissipative particle dynamics (DPD), blood cell models are constructed using DPD particles and thus are naturally assimilated with the background flow, continuum-based RBC models often implemented a boundary integral algorithm or the immersed boundary method (IBM) to couple RBC models with the background flow, which are solved using different solvers, including the finite volume method, the finite element method and the lattice Boltzmann method [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Motivated by experimental studies, recent progress in computational modeling has enabled simulations of fluid dynamics and cell aggregation dynamics under physiological and pathological states [ 10 , 27 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], which has provided insight into the pathogenesis of the disease as well as facilitated the development of therapeutic treatments [ 51 , 52 ]. For example, RBC models developed using DPD are widely applied to simulate the deformation and aggregation of healthy RBC doublets [ 42 ] together with their effects on the blood cell dynamics in stenosed microvessels [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stacks of beads may provide slits of less than 1 ÎĽm in width but do not allow controlled and extensive studies (14). Recent numerical and/or theoretical approaches have suggested that the spleen may play an important role in defining the surface area-to-volume ratio of the RBCs circulating in the microvascular system (19–24), but, so far, numerical approaches are not quantitatively validated by experiments and no experimental direct observation of RBCs flowing in splenic-like slits supports this hypothesis. Moreover, observations (25, 26) also suggest that slit caliber may vary over time leading to the hypothesis and modeling (27) that it is modulated by stress fiber contraction in human endothelial cells.…”
mentioning
confidence: 99%
“…Stacks of beads may provide slits 36 of less than 1 µm in width but do not allow controlled and 37 extensive studies (14). Recent numerical and/or theoretical 38 approaches have suggested that the spleen may play an impor-39 tant role in defining the surface area-to-volume ratio of the 40 RBCs circulating in the microvascular system (19)(20)(21)(22)(23)(24), but, so…”
mentioning
confidence: 99%